(3JSOjO GdYbGFO aj TQM JLQjO GdahGFOs - (3GdCUagGfj, GdCUHgGfj, CHh GdKfGA, TeS GdOjf, eMehO Hf YHO GdQMef Hf CMeO, J (B749(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3deG cGf CYdi eG JSeh Edjg CYfGb Gdgee hCLd eG jJfGaS aj CNHGQ GdCee JMdjI GdfaS HGdYdhe GdJj ef CUfGagG KeQGJ GdYbhd JLJHi (B....s
(3BNQgG (B:s
.... (3Hd YO GdYbd hGdfaS Yf GdQhMGfj hgh jMJed ZjQ eG bdJ Cfg HUOO VHW CbSGe GdLhgQ Ydi QCjge agPG GdMed HYjO Yf cdGeg ZjI GdHYO (B.s
(3JHUQI GdeDda (B:s
(3aj GdcTa (B1\346 (3Jhaj (B746s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B7/176s
(3cTa GdXfhf (B1/346s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds